Efficacy and Safety of Subcutaneous Esketamine in the Treatment of Suicidality in Major Depressive Disorder and Bipolar Depression - Surjan, Juliana; Grossi, Julia Diniz; Del Porto, José Alberto; Delfino, Rodrigo Simonini; de Oliveira Cerqueira, Raphael; Lucchese, Ana Cecília; Magalhães, Eduardo; Del Sant, Lorena Catarina; Tuena, Marco Aurélio; Nakahira, Carolina; Fava, Victor Augusto Rodovalho; Steglich, Matheus Souza; et al. (Clinical drug investigation, 2022)
Background and Objective Affective disorders account for most cases of suicide. The pharmacological arsenal to treat suicidality is limited and available agents take too long to take effect. A large body of evidence shows optimal results of ketamine for treating depression, but the evidence concerning suicidality has not been fully described. We report the first real-world study of severely depressed patients presenting with suicide ideation who were treated with repeated administration of subcutaneous esketamine. Methods We analyzed data from 70 acutely depressed subjects diagnosed with resistant major depressive disorder or bipolar depression. Subjects were administered subcutaneous esketamine once a week for 6 weeks. The primary efficacy endpoint, the change from baseline to 24-h post-administration 6 in the item 10 Montgomery–Åsberg Depression Rating Scale score, was analyzed using a mixed-effects repeated-measures model. Results There were significant effects for time on item 10 Montgomery–Åsberg Depression Rating Scale scores ( p < 0.0001) but not for a time × diagnosis interaction ( p = 0.164) from baseline to the end of the study. Efficacy of esketamine did not differ between groups (major depressive disorder vs bipolar depression) at any timepoint. Statistical significance on suicidality scores was observed from 24 h after the first administration ( p < 0.001), and a further reduction was observed with repeated administrations. Esketamine was safe and well tolerated. Mean heart rate remained stable during the administrations and the blood pressure increase was self-limited. Conclusions Repeated subcutaneous esketamine administration had significant anti-suicidality effects in both major depressive disorder and bipolar groups, with a rapid onset of action and a good tolerability profile. Large randomized controlled trials are warranted to confirm these preliminary findings.